Gait characteristics related to fall risk in patients with cerebral small vessel disease - Wang, Yajing; Li, Yanna; Liu, Shoufeng; Liu, Peipei; Zhu, Zhizhong; Wu, Jialing (Frontiers in Neurology, 2023)
Background: Falls and gait disturbance are significant clinical manifestations of cerebral small vessel disease (CSVD). However, few relevant studies are reported at present. We aimed to investigate the gait characteristics and fall risk in patients with CSVD. Methods: A total of 119 patients with CSVD admitted to the Department of Neurology at Tianjin Huanhu Hospital between August 17, 2018 and November 07, 2018 were enrolled in this study. All patients underwent cerebral magnetic resonance imaging scanning and a 2-min walking test using an OPAL wearable sensor and Mobility Lab software. Relevant data were collected using the gait analyzer test system to further analyze the time-space and kinematic parameters of gait. All patients were followed up, and univariate and multivariate logistic regression analyses were done to analyze the gait characteristics and relevant risk factors in patients with CSVD at an increased risk of falling. Results: All patients were grouped according to the presence or absence of falling and fear of falling, and were divided into a High Fall Risk group (n = 35) and Low Fall Risk group (n = 72). Logistic multivariate regression analysis showed that toe off angle (Odds Ratio (OR) = 0.742, 95% Confidence Interval (CI) 0.584–0.942, p <0.05), toe off angle Coefficient of Variation (CV)(OR = 0.717, 95% CI: 0.535–0.962, p <0.05), stride length CV (OR = 1.256, 95% CI: 1.017–1.552, p <0.05), and terminal double support CV (OR = 1.735, 95% CI: 1.271–2.369, p <0.05) were statistically significant (p <0.05) and were independent risk factors for high fall risk in patients with CSVD. Conclusion: The high fall risk in patients with CSVD is closely related to the time-space and kinematic parameters of gait, gait symmetry, and gait variability. In particular, toe-off angle, toe-off angle CV, stride length CV, and terminal double support CV are independent risk factors for high fall risk in patients with CSVD.